Web-based e-commerce application for SARODA Furniture (SARODA Furniture website) / Mohd Khairul Annuwar Saleh - Saleh, Mohd Khairul Annuwar (2012)
In the globalization era today, the emergence of personalization application for online shopping in business industries is new approach to help business owners gain most benefits for their companies. E-Commerce, with the Internet as its main platform has a very large market network. Because of these, an application development for online shopping system will be developed for SARODA Furniture named as Web-Based E-Commerce Application for SARODA Furniture and known as SARODA Furniture Websites. The development of the system is to help customer to find their product based on their preference, they can customize and personalize the certain product that their want. The system provides facilities for customers to place order, purchase and a recommend product based on customer needs electronically. The system developed in the Windows environment using PHP as the scripting language. While, MySQL is used as the database management system. Besides that, the XML element, CSS and AJAX also will be used in developing some requirement for this system. In developing this system the System Development Life Cycle (SDLC) under Waterfall Model Process has been implemented as the main framework of the project study.